TRENDS IN INCIDENCE AND MORTALITY FROM PANCREATIC CANCER IN CENTRAL SERBIA, IN THE PERIOD FROM 1999 TO 2019 - Muratovic, Belma; Nikolić, Aleksandra M; Grujicic, Sandra (HEALTH CARE, 2022)
Introduction: Pancreatic cancer is the fourteenth leading cause of disease and the seventh leading cause of death among all malignant diseases. The aim of the research was to analyze the trends in the incidence and death of pancreatic cancer in central Serbia for the period 1999-2019. years.Methods: The data about diseased and dead, as well as population by sex and age, in the period 1999-2015 were taken over from the Cancer registry of Central Serbia, and the data for 2016, 2017, 2018 and 2019 were obtained from the Institute of Public Health of Serbia. Based on obtained data, we counted crude, specific and standardized rates of incidence and mortality for pancreatic cancers, for all ages. Trends rate in incidence and mortality were counted using joinpoint regression analysis.Results: In the period 1999-2019. In central Serbia, the average annual number of patients was 378 men and 305 women, and the average number of deaths was 406 men and 336 women. The average annual standardized incidence rate (per 100,000) was 7.7 for men and 5.0 for women, and the standardized mortality rate (per 100,000) was 7.9 for men and 5.1 for women. In men, the highest average annual agespecific incidence rate was recorded at the age of 60-69 (39.7 per 100,000), and the mortality rate at the age of 70 and over (42.4 per 100,000). Among women, the highest incidence and mortality rates were in the oldest age (70 and over) and were 25.7 and 34.8 per 100,000. During the observed period, there was a significant increase in standardized incidence rates for men of 2.9% and for women of 3.7% per year. Also, a trend of increasing standardized mortality rates was observed in men (of 1.2%) and women (of 0.6%), but significance was achieved only in men.Conclusion: In the period 1999-2019. in central Serbia, incidence and mortality rates are on the rise. Research on risk factors for the development of this disease is necessary in order to take preventive measures. Also, early detection and timely therapy should contribute to the reduction of death from this malignancy
Keywords: pancreatic cancer, incidence, mortality, trend, joinpoint regression analysis